1999
DOI: 10.1046/j.1471-4159.1999.0720120.x
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Caveolae Microdomains in Extracellular Signal‐Regulated Kinase and Focal Adhesion Kinase Activation Induced by Endothelin‐1 in Primary Astrocytes

Abstract: Endothelin-1 (ET-1) mitogenic activity in astrocytes is mediated by the activation of the extracellular signal-regulated kinase (ERK) pathway together with the Rho-dependent activation of the focal adhesion kinase (FAK) pathway. To clarify the mechanisms responsible for the coordinate activation of both pathways in the ET-1 signal propagation, the involvement of caveolae microdomains, suggested to play a role in signal transduction, was evaluated. In this study, it is reported that caveolae of primary astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 35 publications
6
47
1
Order By: Relevance
“…Caveolae are low density membrane microdomains that have been implicated in initiating the signaling events induced by growth factors, such as epidermal growth factor and endothelin-1, and receptors for these ligands are enriched within caveolae. 17 As expected, caveolin-1, a characteristic caveolar marker protein in the brain, 18 appeared to be retained in the Triton X-100 -insoluble fraction under basal conditions and after ICAM-1 crosslinking ( Figure 5D). Under basal ( Figure 5A) and ICAM-1 cross-linking conditions (data not shown), ICAM-1 and caveolin-1 showed no significant colocalization in GP8/3.9 cells, although data from sucrose density gradient fractionation of GP8/3.9 cell lysates showed that caveolin-1 and ICAM-1 cofractionated ( Figure 5C).…”
Section: Icam-1 and Caveolin-1 Cofractionate On Sucrose Density Gradisupporting
confidence: 70%
“…Caveolae are low density membrane microdomains that have been implicated in initiating the signaling events induced by growth factors, such as epidermal growth factor and endothelin-1, and receptors for these ligands are enriched within caveolae. 17 As expected, caveolin-1, a characteristic caveolar marker protein in the brain, 18 appeared to be retained in the Triton X-100 -insoluble fraction under basal conditions and after ICAM-1 crosslinking ( Figure 5D). Under basal ( Figure 5A) and ICAM-1 cross-linking conditions (data not shown), ICAM-1 and caveolin-1 showed no significant colocalization in GP8/3.9 cells, although data from sucrose density gradient fractionation of GP8/3.9 cell lysates showed that caveolin-1 and ICAM-1 cofractionated ( Figure 5C).…”
Section: Icam-1 and Caveolin-1 Cofractionate On Sucrose Density Gradisupporting
confidence: 70%
“…This observation of possible caveolae involvement differs from those noted by others, who described chemokine-induced receptor internalization to be achieved by the more commonly acknowledged clathrincoated pit pathway (33)(34)(35). Insofar as caveolae and their main structural protein, caveolin-1, both of which are expressed by astrocytes (36,37), have been implicated in regulating signal transduction events as well as subserving endocytosis and transcytosis (38), caveolin-1-bearing membrane domains may be critical in mediating one or more of the responses of astrocytes to stimulation by MCP-1.…”
contrasting
confidence: 78%
“…It may be relevant in regard to endothelin-induced contraction that both ET A and ET B receptors have been proposed to depend on caveolae (3,35). The present results showed that impaired contractility in response to ET-1 in the ileum was not associated with reduced ET-1 receptor expression, nor was it due to reduced Ca 2ϩ sensitization.…”
Section: Discussionsupporting
confidence: 43%